Czech Women's Point of Views on Immediate Breast Reconstruction after Mastectomy due to BRCA Gene Mutation or Breast Cancer - Ventruba, Tomáš; Ješeta, Michal; Minář, Luboš; Vomela, Jindřich; Brančíková, Dagmar; Žáková, Jana; Ventruba, Pavel (Healthcare (Basel, Switzerland), 2023)
(1) Objective: Breast cancer is the most common cancer in women, and the incidence of the disease continues to increase. The issue of immediate breast reconstruction (IBR) in women with BRCA mutations and breast cancer is highly topical. This study is based on the long-term experience of our workplace with the diagnosis and treatment of breast cancer in women. We use the possibilities of oncoplastic surgery, including IBR. Our effort involves learning about women's awareness of IBR with a mastectomy at the same time. (2) Methods: The method of quantitative research of women's awareness using a structured anonymous questionnaire was chosen. Out of the total number of 84 respondents who already underwent IBR, 36.9% were due to BRCA mutations, and 63.1% were due to breast cancer. (3) Results: All of the respondents learned about the possibility of IBR before treatment or during treatment planning. The information was first obtained mainly from an oncologist. Women obtained the most information regarding IBR from a plastic surgeon. Before the mastectomy, all of the respondents already knew what IBR meant, as well as about the payment of IBR by the health insurance company. All of the respondents would choose the IBR option again. A total of 94.0% of women cited preservation of body integrity as a reason for undergoing IBR, and 88.1% of women knew about the possibility of performing IBR with their own tissues. (4) Conclusions: There are few specialized centers with a team of experts in reconstructive breast surgery in the Czech Republic, especially those that perform IBR. Research has shown that all of the patients were well informed about IBR, but the vast majority only learned about IBR before the surgical procedure was planned. All of the women wished to maintain body integrity. Our study results in the recommendations for patients and for healthcare management.
Keywords: mastectomy; questionnaire study; patient awareness; BRCA mutations; immediate breast reconstruction; breast cancer